2014
DOI: 10.1007/s11033-014-3409-x
|View full text |Cite
|
Sign up to set email alerts
|

RSPO fusion transcripts in colorectal cancer in Japanese population

Abstract: R-spondin (RSPO) gene fusions have recently been discovered in a subset of human colorectal cancer (CRC) in the U.S. population; however, whether the fusion is recurrent in CRC arising in patients from the other demographic areas and whether it is specific for CRC remain uncertain. In this study, we examined 75 primary CRCs and 121 primary lung cancers in the Japanese population for EIF3E-RSPO2 and PTPRK-RSPO3 fusion transcripts using RT-PCR and subsequent sequencing analyses. Although the expression of EIF3E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 19 publications
8
38
0
Order By: Relevance
“…Here, we identified a recurrent RSPO2 gene rearrangement due to a 46.4 kb microdeletion on chromosome 8q23.1 as the most prevalent cause of activated β-catenin signalling in HCA with wild-type CTNNB1 gene as demonstrated by targeted ultra-deep sequencing and independent validation using AMP-based NGS translocation detection. An identical microdeletion was previously described in colorectal cancer 34. Here, it was demonstrated that upstream of RSPO2 , a 351 bp SINE was fused to exon 1 of the eukaryotic translation initiation factor 3 subunit E ( EIF3E ) gene.…”
Section: Discussionsupporting
confidence: 60%
“…Here, we identified a recurrent RSPO2 gene rearrangement due to a 46.4 kb microdeletion on chromosome 8q23.1 as the most prevalent cause of activated β-catenin signalling in HCA with wild-type CTNNB1 gene as demonstrated by targeted ultra-deep sequencing and independent validation using AMP-based NGS translocation detection. An identical microdeletion was previously described in colorectal cancer 34. Here, it was demonstrated that upstream of RSPO2 , a 351 bp SINE was fused to exon 1 of the eukaryotic translation initiation factor 3 subunit E ( EIF3E ) gene.…”
Section: Discussionsupporting
confidence: 60%
“…However, the association between RSPO and cancer has not been extensively studied. Studies on the role of RSPO2 in cancer primarily focus on colon tumors (14,15). A recent study reported that high-copy amplifications of RSPO2 gene were observed in 231 HCC cases via whole exome sequencing (25).…”
Section: Discussionmentioning
confidence: 99%
“…1A and Supplementary Table S2), had not been identified by the in vitro functional assay, maybe due to the low sensitivity of the assay. It has been reported that RSPO2 and RSPO3 genes are targets of rearrangements in colon cancer and that resulting fusions increase gene expression (29,31). On the basis of these reports, we performed a PCR-based screen and also mRNAseq analysis.…”
Section: Identification Of Rspo As a Tumor-derived B-catenin Stimulatmentioning
confidence: 99%
“…Ectopic expression of Rspo2 was shown to increase tumorigenic and invasive properties of mouse breast cell lines (25). Genomic rearrangements and transcriptional activation in human tumors that result in elevated RSPO expression have been identified, suggesting that RSPO may be functionally important for tumor development (29)(30)(31)(32). However, no direct demonstration of a functional role for RSPO in cancer development and maintenance has been reported to date.…”
Section: Introductionmentioning
confidence: 99%